Odpowiedzi

2009-11-30T15:20:26+01:00
⅙ (x-1)=1
1/6x-1/6=1
1/6x=1+1/6
1/6x=7/6
x=7 spr 1/6*(7-1)=1/6*6=1

-2(2x-1)= ¾ x
-4x+2=3/4x
-4x-3/4x=-2
-16/4x-3/4x=-2
-19/4x=-2
x=8/19
spr -2(2*8/19-1)= ¾ *8/19
-2*(-3/19)=6/19
6/19=6/19

¾ (2-3x)= -6
6/4-9/4x=-6
-9/4x=-6-6/4
-9/4x=-30/4
x=30/9
spr ¾ (2-3*(30/9))=3/4*(2-10)=3/4*(-8)=-6

⅕(x-3) =9- x
1/5x-3/5+x=9
6/5x=9+3/5
6/5x=48/5
x=8

spr ⅕(8-3) =9- 8
1/5*5=1
1=1
2009-11-30T16:58:53+01:00
1.
⅙(x-1) =1
⅙x-⅙=1
⅙x=1⅙
x=7/6*6/1=7
x=7

spr.⅙(7-1)=1
1=1
2.
-2(2x-1)=¾x
-4x-¾=-2
-4¾x=-2
x=2*4/19=8/19
spr.

-2(2*8/19-1)=¾*8/19
-2*3/19=6/19
6/19=6/19
3.
3/4(2-3x)=-6
3/2-9/4x=-6
-9/4x=-6-3/2
-9/4x=-4½
x=9/2*4/9=2
x=2

spr.
3/4(2-3*2)=-6
-6=-6
4.
1/5(x-3)=9-x
1/5x-3/5=9-x
6/5x=9+3/5
2/5x=48/5
x=48/5*6/2=72/5
2009-11-30T19:25:22+01:00
1/6(x-1)=1
1/6x-1/6=1
1/6x=1+1/6
1/6x=7/6 |*6
x=7
spr.:
1/6(7-1)=1
1/6*6=1
6/6=1
1=1

-2(2x-1)=3/4x |*4
-8(2x-1)=3x
-16x+8=3x
-16x-3x=-8
-19x=-8 |:(-19)
x=8/19
spr.:
-2(2*8/19-1)=3/4*8/19
-2(16/19-1)=6/19
-2*(-3/19)=6/19
6/19=6/19

3/4(2-3x)=-6 |*4
3(2-3x)=-24
6-9x=-24
-9x=-24-6
-9x=-30 |:(-9)
x=10/3
spr.:
3/4(2-3*10/3)=-6
3/4(2-10)=-6
3/4*(-8)=-6
-6=-6

1/5(x-3)=9-x |*5
x-3=45-5x
x+5x=45+3
6x=48 |:6
x=8
spr.:
1/5(8-3)=9-8
1/5*5=1
1=1